(untitled) (Research, Society and Development, 2021)
This article presents a bibliographic review, which is part of a research under construction, on the development of digital fluency in the reinvention of teaching practice, in the current context mediated by technology. The purpose of this text is to dialogue with the main studies in the areas of Pedagogical Practices and Technology, to identify gaps that can still be filled in research in Education. The bibliographic survey was carried out by searching the database of the Scielo Electronic Library, from which three articles were selected. This study points out that, although technological resources in the context of the need for remote education are present and linked to a process of reinventing pedagogical practice, there will be no guarantee of the development of digital fluency if there is no investment in teacher training for the use of technologies in Education.